Modeling of wind gap formation and development of sedimentary basins during fold growth: application to the Zagros Fold Belt, Iran. Issue 11 (14th March 2016) - Collignon, Marine; Yamato, Philippe; Castelltort, Sébastien; Kaus, Boris J. P.
Abstract: Mountain building and landscape evolution are controlled by interactions between river dynamics and tectonic forces. Such interactions have been extensively studied, however a quantitative evaluation of tectonic/geomorphic feedbacks, which is imperative for understanding sediments routing within orogens and fold‐and‐thrust belts, remains to be undertaken. Here, we employ numerical simulations to assess the conditions of uplift and river incision necessary to deflect an antecedent drainage network during the growth of one, or several, folds. We propose that a partitioning of the river network into internal (endorheic) and longitudinal drainage arises as a result of lithological differences within the deforming crustal sedimentary cover. Using examples from the Zagros Fold Belt (ZFB), we show that drainage patterns can be linked to the non‐dimensional incision ratio R between successive lithological layers, corresponding to the ratio between their relative erodibilities or incision coefficients. Transverse drainage networks develop for uplift rates smaller than 0.8 mm yr −1 and low incision ratios (−10 < R < 10). Intermediate drainage networks are obtained for uplift rates up to 2 mm yr −1 and large incision ratios ( R > 20). Parallel drainage networks and the formation of sedimentary basins occur for large values of incision ratio ( R > 20) and uplift rates between 1 and 2 mm yr −1 . These results have implications for predicting the distribution of sediment depocenters in fold‐and‐thrust belts, which can be of direct economic interest for hydrocarbon exploration. They also put better constraints on the fluvial and geomorphic responses to fold growth induced by crustal‐scale tectonics. Copyright © 2016 John Wiley & Sons, Ltd.